The Influence Of Social Media On Radio Listener Loyalty - Kustiawan, Winda; Hasibuan, Ahmad Aswari; Fitri, Amanda Syah; Hsb, Fajar Ramadhan; Daulay, Fikri Afdillah; Sitorus, Nadila Putri Br; Afriani, Rani; Padang, Ranto Pradana (LPPPIPublishing, 2024)
This research aims to investigate the influence of social media on radio listener loyalty through a qualitative approach. In the digital era, social media has become an important tool for radio stations to interact with their listeners. This study uses qualitative methods with in-depth interview techniques and participant observation to collect data from 30 radio listeners who actively use social media. Data analysis was carried out using the thematic analysis method to identify emerging patterns and themes related to social media use and listener loyalty. The research results show that interaction via social media plays an important role in building and strengthening radio listener loyalty. Listeners who feel engaged and valued through interactive and communicative content on platforms like Facebook, Twitter and Instagram tend to have strong emotional ties to radio stations. These findings indicate that social media is not only a promotional tool but also a means of building a loyal community of listeners. The practical implication of this research is the importance of radio stations integrating social media strategies in their operations and marketing in order to maintain and increase listener loyalty. Further research is recommended to explore the specific role of different types of social media content in building listener loyalty.